Skeletal Muscle Signaling Following Whole-Body and Localized Heat Exposure in Humans - Ihsan, Mohammed; Deldicque, Louise; Molphy, John; Britto, Florian; Cherif, Anissa; Racinais, Sebastien (Frontiers in Physiology, 2020)
This study identified the changes in hypertrophy/atrophy and mitochondrial-related signaling in human skeletal muscle following whole-body (WB) and localized single leg (SL) heat treatment. Nine active male participants were administered either 60 min of passive WB (44-50˚C, 50% humidity) or SL (water-perfused suit at 49.5 ± 1.4˚C) heat treatment at least 1 week apart in a counterbalanced order. The untreated leg during SL was considered as control (CON). Core, skin and quadriceps muscle temperature were monitored throughout the experimental trials. Muscle microbiopsy samples were obtained prior to (PRE), and 30 min and 3 h post (POST) following heat treatment. Muscle temperature increased with time (p<0.0001) in both WB and SL, with no differences between conditions (38.8 ± 0.5˚C vs. 38.1 ± 0.6˚C, p=0.065). Core temperature increased only following WB, and was significantly higher compared with SL (39.1 ± 0.3˚C vs. 37.1 ± 0.1, p<0.0001). Compared with PRE, WB up-regulated the phosphorylation status of the majority of the Akt/mTOR pathway (Akt, mTOR, S6K1, rpS6 and p-eIF4E; p≤0.050), with the exception of 4EBP1 (p=0.139). WB also increased the mRNA of HSPs 72, 90and 25 (all p<0.021), and increased or tended to increase the phosphorylation of FOXO1 (p=0.066) and FOXO3a (p=0.038). In addition, most (NRF1, NRF2, COX2 and COX4-I2; all p≤0.050), but not all (CS, Cyt c and COX4-I1; p>0.441) mRNA content indicative of mitochondrial biogenesis were increased following WB, with no changes evident in these parameters in SL or CON (all p>0.090). These results indicate that 1 h of whole-body heat treatment enhanced anabolic (Akt/mTOR), mitochondrial and cyto-protective signaling (HSP), with a concomitant possible inhibition of FOXO transcription factors.